Quality of the scholastic environment for a Physically Handicapped and its relation with some variables Field research in special education schools in Damascus city - Zahlok , Maha; Salhab , Sarab (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The recent search aims at recognize the quality of the scholastic environment for a handicapper and its relation with some variables (sex, age). A sample consisting of (112) handicapped children who study in special schools and they are between 7-14 years old. A questionnaire of quality for scholastic environment has been applied as the handicapped children realize it, and it is prepared, in order to recognize the scholastic environment for a Physically Handicapped. The questionnaire has been included (70) items. Pilot sample consisted of (22) handicapped children, Reliability was established by Cronbach – Alpha Reliability at lest (0.965) and (0.922) in Test – Retest. The final results showed that realization for the quality of the scholastic environment were middle rated. Also there are differences which have statistical significance between the two categories 7 less of 10, 10 less of 14) according to scholastic environment questionnaire, and it is for the benefit of this category categories 7 less of 10, that the category 10 less of 14 of handicappers has the wish to depend on themselves in carrying out their daily needs. The environment will not be an obstacle. Perhaps this preferring returns to the oldest handicapper's wish to appear powerful and able to live a normal life. The handicapper does this to shatter the inferiority image that he may think others are looking at him through it, unlike the youngest category. In addition to, there are no differences which have statistical significance between males and females according to the questionnaire of quality for scholastic environment, that the unequipped scholastic environment carries out all the handicapped students' needs is a common problem between both males and females.